Drug action at the 5-HT(1A) receptor in vivo: autoreceptor and postsynaptic receptor occupancy examined with PET and [carbonyl-(11)C]WAY-100635. - Rabiner, E; Gunn, R; Wilkins, MR; Sargent, P; Mocaer, E; Sedman, E; Cowen, P; Grasby, P (2000)
Serotonin(1A) (5-HT(1A)) receptors have been implicated in the pathophysiology and treatment of anxiety and depression and are a target for novel drug development. In this qualitative study, positron emission tomography (PET) and [carbonyl-(11)C]WAY-100635 were used to assess 5-HT(1A) autoreceptor and postsynaptic receptor occupancy in man in vivo by five different compounds with nanomolar affinity for this site. Occupancy by pindolol, penbutolol, buspirone, EMD 68843, and S 15535 was compared to test-retest data from 10 healthy volunteers. All drugs, apart from buspirone, displayed occupancy at the 5-HT(1A) receptor site. Pindolol demonstrated a preferential occupancy at the autoreceptor compared to the postsynaptic receptor over a plasma range of about 10-20 ng/mL. Differential occupancy may be an important component of novel drug action. The level of autoreceptor or postsynaptic occupancy needed to achieve significant physiological effects is not known, although it is of note that none of the drugs in this study achieved occupancies beyond 60%. Overall this study demonstrates the utility of PET in aiding novel drug development.